The Influence of Promotion and Reputation on Purchase Decisions of Pegadaian Gold Saving Products (Study on Customers of Syariah Gold Savings Account, Pegadaian Syariah Bandar Lampung Branch) - Siti Khulwaniatur Risya; Aida Sari; Dwi Asri Siti Ambarwati (Inovbook Publications, 2023)
Gold is considered an investment with relatively low risk and its value is almost always profitable because it is an investment object whose value tends to increase, thereby increasing public interest in investing in gold. Pegadaian Syariah, which is part of PT. Pegadaian, has innovated by releasing a product called Gold Savings with the aim of facilitating people who want to own gold at an affordable price and with minimal capital by saving. However, in recent years there has been a decrease in the number of Gold Savings customers at the Radin Intan Sharia Pawnshop which was influenced by the promotion factors carried out and the company's reputation. So that, in this study discusses promotion and reputation on customers' decisions to buy Gold Savings products at the Radin Intan Sharia Pegadaian Branch using the nonprobability sampling method using the Purposive Sampling method category, with a total sample of 140 respondents. This study uses multiple linear regression analysis and partial hypothesis testing (t-test). The results obtained in this study indicate that promotion and reputation have a positive and significant effect on purchasing decisions for Gold Savings products at the Radin Intan Branch Sharia Pawnshop with a total sample of 140 respondents. This study uses multiple linear regression analysis and partial hypothesis testing (t-test). The results obtained in this study indicate that promotion and reputation have a positive and significant effect on purchasing decisions for Gold Savings products at the Radin Intan Branch Sharia Pawnshop with a total sample of 140 respondents. This study uses multiple linear regression analysis and partial hypothesis testing (t-test). The results obtained in this study indicate that promotion and reputation have a positive and significant effect on purchasing decisions for Gold Savings products at the Radin Intan Branch Sharia Pawnshop.